Calon GuruKonseptualisasi Profesionalisme: Perspektif Calon Guru Sains dan Agama di Perguruan Tinggi Islam - Albertos Damni (Institut Agama Islam Negeri Kerinci, 2023)
This study explores prospective science and religion teachers' perceptions of professionalism within Islamic education at Islamic universities. Purposive sampling was used, and in-depth interviews were conducted with 17 students, including nine science majors and eight religion majors. Thematic data analysis was employed to examine the views, values, and practices that underpin their understanding of professionalism. The findings reveal that prospective Science teachers emphasize the significance of deep and applicable scientific mastery, while prospective Religion teachers prioritize moral and spiritual professionalism in teaching Islamic values. Both groups, however, concur that professionalism encompasses integrity, good teaching ethics, and a commitment to the mission of Islamic education. Factors such as the educational environment, institutional policies, and societal expectations significantly influence their perceptions. This study provides valuable insights into how professionalism is conceptualized and practiced within Islamic education, highlighting the need for more inclusive and relevant teaching approaches. These findings offer a foundation for enhancing educational policies and practices to better develop professionalism among future educators in Islamic higher education institutions.